Cloning and nucleotide sequence of a gene (ompS) encoding the major outer membrane protein of Legionella pneumophila. - Hoffman, P S (1992)
The major outer membrane protein of Legionella pneumophila is composed of 28- and 31-kDa subunits cross-linked by interchain disulfide bonds. The oligomer is covalently anchored to the underlying peptidoglycan via the 31-kDa subunit. We have cloned the structural gene ompS encoding both proteins. Oligonucleotide probes synthesized from the codons of the N-terminal amino acid sequence of purified 28- and 31-kDa subunits were used to identify cloned sequences. A 2.9-kb HindIII fragment cloned into pBluescript (clone H151) contained the ompS gene. Nucleotide sequence analysis revealed an open reading frame of 891 bp encoding a polypeptide of 297 amino acids. A leader sequence of 21 amino acids was identified, and the mature protein contained 276 amino acids. The deduced amino acid sequence of OmpS matched the experimentally determined amino acid sequence (32 amino acids), with the exception of two cysteine residues. The deduced amino acid sequence was rich in glycine and aromatic amino acids and contained four cysteine residues, two in the amino terminus and two in the carboxy region. Primer extension analysis (total RNA from L. pneumophila) identified the transcription start at 96 to 98 bp upstream of the translation start, but no Escherichia coli-like promoter sequences were evident. While an mRNA transcript from clone H151 was detected, no cross-reactive protein was detected by immunoblotting with either monoclonal or polyclonal antibody. Attempts to subclone the gene in the absence of the putative promoter region (i.e., under the control of the lac promoter) proved unsuccessful, possibly because of overproduction lethality in E. coli. The ompS DNA sequence was highly conserved among the serogroups of L. pneumophila, and related species also exhibited homology in Southern blot analysis at a moderately high stringency. Evidence is presented to suggest that this gene may be environmentally regulated in L. pneumophila.